HF communication between India-Antarctica during 1992, and its dependence on a) Geomagnetic activity, b) Season - Jeeva, K.; Hanchinal, A.N.; Dhar, Ajay; Daga, D.M.; Rajaram, G. (My University, 1995)
Observations made at the Indian station Maitri in East Antarctica during the period spanning between July 1992 and January 1993, reveal that the state of HF communication between India and Antarctica is greatly dependent on the electromagnetic state of Earth's environment (as depicted by magnetograms). It is noticed that the radio signal intensity is also dependent on season. Present work reports on some of these observations.
Keywords: HF Communication